2014
DOI: 10.1038/nature13998
|View full text |Cite
|
Sign up to set email alerts
|

Experimentally induced innovations lead to persistent culture via conformity in wild birds

Abstract: In human societies, cultural norms arise when behaviours are transmitted with high-fidelity social learning through social networks1. However a paucity of experimental studies has meant that there is no comparable understanding of the process by which socially transmitted behaviours may spread and persist in animal populations2,3. Here, we introduce alternative novel foraging techniques into replicated wild sub-populations of great tits (Parus major), and employ automated tracking to map the diffusion, establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
743
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 617 publications
(786 citation statements)
references
References 38 publications
22
743
2
Order By: Relevance
“…starting from a random mixture of the two behaviours, but it clearly shows that different analysis may lead to different results. More specifically, in this case, the analysis based on individuals reveals perfect linearity, in keeping with the individual level random copying default, whereas the analysis based on behaviours reveals the sigmoidal relation between copying probability and relative frequency characteristic of conformist transmission (see Aplin et al, 2015b). In other words, the analysis based on behaviours leads to a detection of conformist transmission where clearly there is none (because all copying here is random).…”
Section: Methodsological Concern For Using the Majority Of 'Behavioursmentioning
confidence: 99%
See 3 more Smart Citations
“…starting from a random mixture of the two behaviours, but it clearly shows that different analysis may lead to different results. More specifically, in this case, the analysis based on individuals reveals perfect linearity, in keeping with the individual level random copying default, whereas the analysis based on behaviours reveals the sigmoidal relation between copying probability and relative frequency characteristic of conformist transmission (see Aplin et al, 2015b). In other words, the analysis based on behaviours leads to a detection of conformist transmission where clearly there is none (because all copying here is random).…”
Section: Methodsological Concern For Using the Majority Of 'Behavioursmentioning
confidence: 99%
“…Specifically, we note that the gold standard to evidence conformist transmission has been to identify a sigmoidal relation between individuals' probability of copying the majority and the proportional majority size (e.g. see Aplin et al, 2015b;Battesti et al, 2015;Boyd & Richerson, 1985;Chou & Richerson, 1992;Claidiere, Bowler, & Whiten, 2012; but see Acerbi, van Leeuwen, Haun, & Tennie, 2016). A simple agent-based model may help illustrate one of the problems arising from considering the frequencies of behaviours, instead of the frequencies of individuals, in detecting this sigmoidal signature of conformist transmission.…”
Section: Methodsological Concern For Using the Majority Of 'Behavioursmentioning
confidence: 99%
See 2 more Smart Citations
“…showed that nine-spined sticklebacks abandoned a food patch they had previously learned was optimal when they observed a demonstrator feeding at a higher-payoff patch. Conformity has been demonstrated in stickleback and great tits (Aplin et al 2014), with an individual fish or bird disproportionately more likely to feed at a location where a majority of other individuals had fed. These studies with phylogenetically diverse species show that adaptive social learning rules likely evolved independently in response to particular ecological conditions rather than exclusively in our own species' recent ancestors.…”
Section: Social Learning Is Payoff-biased and Conformistmentioning
confidence: 99%